The perception of guidance and counselling to the grade- IX and grade-XII pupils – an investigation of Petauke district schools of eastern province of Zambia - Tamilenthi, S; Mbewa, Charles Tobias (International Multidisciplinary Research Journal, 2012)
This study looked at the impact of guidance and counselling services to grade nine (9) and twelve (12) pupils in high and basic schools in Petauke District in the Eastern Province of Zambia. This study targeted twenty five grade nine pupils and twenty five grade twelve pupils a total of fifty respondents. These respondents were sampled from Mizyu basic, Petauke basic, Inusa private basic, Kawere basic schools, Petauke high school and Petauke Day school. The questionnaire is consisting of 20 questions from 2 sections. The collected information is converted to table form in order to analyze the impacts. The software SPSS used for the analysis and to draw the results. The suitable recommendations are given according to the results were drawn from the study. The recommendations will help the students of Grade IX and Grade XII to enhance utility of guidance and counselling service provided by the schools. The findings also will help the Government through the Ministry of Education to improve organisation of guidance and counselling services and activities in schools. In view of this most pupils revealed that very little was done in the areas of guidance and counselling especially on career and heath information. The findings indicated that there is need for a comprehensive professional program for pupils on guidance and counselling education.